Attention on low risk prenatal under the perspective of puerperal women - Roberta Luciele Blaas dos Santos; Monique Prestes; Sonia Maria Konzgen Meincke; Marilu Correa Soares; Ana Cândida Lopes Corrêa; Camila Neumaier Alves (Universidade Federal de Santa Maria, 2015)
Aim: to know the attention provided to pregnant women during low risk prenatal. Method: a qualitative study, developed with eight women hospitalized in an obstetric unit, from october to november 2013. This study was approved by Research Ethical Committee, under the number 372.047. Data collection occurred through semistructured interviews analyzed under the operative proposal and research in the maternity cards. Results: services showed some treatment weaknesses, such as inappropriate and technicist care. Access difficulties at the Basic Health Unit were identified, what interfered on early identification of pregnant women. Conclusion: there is a gap to be filled by the health services, requiring professional training and promotion of educational actions